Shadow Watch: Unveiling and Mitigating Suspicious Web Threat Interactions - Talib Nadeem Usmani; Zaigham Riaz; Muhammad Zulkifl Hasan; Muhammad Zunnurain Hussain, (Dialogue Social Science Review (DSSR), 2025)
The security of the Web is a significant issue for personal, corporate, and state users in the context of digitalisation. With all kinds of activities related to the Internet growing, different types of threats also emerge, including phishing, malware, ransomware, and others which threaten personal information, funds, and critical system structures. The present paper discusses the principal threats that are inherent in the web environment, the effects of these threats, and protection means. Phishing is a common kind of social engineering that aims at making the target release relevant information. Viruses and worms, in their broad sense, include Malware, which sneaks into systems to corrupt, steal or delete important information. Ransomware is a virus that encrypts a victim’s files and asks for payment for the decryption key. At the same time, drive-by downloads are another virus that installs themselves on a victim’s computer from compromised websites without the victim knowing. With spoofing and man-in-the-middle attacks, data integrity is not preserved. At the same time, SQL injection and cross-site scripting are aimed at controlling web applications in order to control databases. Ddos-attack or Distributed Denial of Service attacks on services knock them off balance by flooding them with traffic. Minimising risks entails keeping oneself posted on the latest developments, updating the software, locking passwords in the cyber world, using a two-factor identification key, and making sure that different strains of technology have backup copies of the materials that have been tampered with. Adhering to security practices and being alert to new threats is vital for an organisation to have a safe online existence. Hence, this study emphasises the need to adopt appropriate measures for evaluating web threats in order to have safe interactions.